Diversity and distribution of arid-semi arid truffle (Terfezia and Picoa) in Elazig-Malatya region of Turkey - Akyuz, M.; Kirbag, S.; Bircan, B.; Gurhan, Y. (Mycosphere Press, 2015)
This work aims to conduct research for finding arid-semi arid (desert) truffles that grow in the Elazig-Malatya area. It was determined that Picoa lefebvrei, P. juniperi, Terfezia olbiensis, T. claveryi and T. boudieri grew naturally in the study areas. Short descriptions of the taxon are provided together with the photograps of fruit bodies and macro-microstructures. In addition, we present new localities for Picoa lefebvrei, P. juniperi, Terfezia olbiensis, T. claveryi and T. boudieri in Turkey. The habitats of these species should be protected by turning the growing fields into natural protected areas.
Keywords: Ascomycotina; arid-semi arid truffle; biodiversity; Helianthemum spp.; hypogeous; Picoa; Terfezia